Semi parametric Estimators for Quantile Model via LASSO and SCAD with Missing Data - Al-Tai, Aws Adnan; Al-Kazaz, Qutaiba N. Nayef (Journal of Economics and Administrative Sciences, 2022)
In this study, we made a comparison between LASSO & SCAD methods, which are two special methods for dealing with models in partial quantile regression. (Nadaraya & Watson Kernel) was used to estimate the non-parametric part ;in addition, the rule of thumb method was used to estimate the smoothing bandwidth (h). Penalty methods proved to be efficient in estimating the regression coefficients, but the SCAD method according to the mean squared error criterion (MSE) was the best after estimating the missing data using the mean imputation method